(p-3q/p-q)*(5q/q)

Simple and best practice solution for (p-3q/p-q)*(5q/q) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (p-3q/p-q)*(5q/q) equation:


x in (-oo:+oo)

((5*q)/q)*(p-((3*q)/p)-q) = 0

((5*q)/q)*(p-3*p^-1*q-q) = 0

5*(p-3*p^-1*q-q) = 0

5 = 0

x belongs to the empty set

x belongs to the empty set

See similar equations:

| -5y=-7+10 | | (8a^3+2a^2-4)+(7a^3-2a+5)= | | −w/20=−2.5 | | 1920*x=30 | | 6=6v+6(v-7) | | 4-3x-1=3x+15 | | -2/5*3/2 | | 1920*x=14 | | 2x+4+58=180 | | 1.2x=14+X | | x^2+x-34=6x+2 | | 1080*x=915 | | 1080-x=165 | | x^2-14x+21=-4x-3 | | -6(4-3x)-7=-2(2-3x) | | 6x-42=10x+40 | | 2(s+2)=8 | | x^2+6x+14=6 | | p/10=7 | | (6a-5)(3a+1)=0 | | 14(4m+11)= | | -5(x-3)+2(a-9)= | | forX^2=324 | | 2x^2+12x+36x=0 | | -5(x-31)=115 | | (2a^2b^4+3ab)+(5ab-2a^2b^4)= | | 10x+11=8x+15 | | 10b-2x=16 | | (-4)x(9)-(5)x(-2)= | | 5[x+3]=2[3x+12] | | 2y=2x-1 | | 2n^2+13n-5=2 |

Equations solver categories